Turner's syndrome in adulthood. - Elsheikh, M; Dunger, D; Wass, J (2002)
Turner's syndrome is the most common chromosomal abnormality in females, affecting 1:2,500 live female births. It is a result of absence of an X chromosome or the presence of a structurally abnormal X chromosome. Its most consistent clinical features are short stature and ovarian failure. However, it is becoming increasingly evident that adults with Turner's syndrome are also susceptible to a range of disorders, including osteoporosis, hypothyroidism, and renal and gastrointestinal disease. Women with Turner's syndrome have a reduced life expectancy, and recent evidence suggests that this is due to an increased risk of aortic dissection and ischemic heart disease. Up until recently, women with Turner's syndrome did not have access to focused health care, and thus quality of life was reduced in a significant number of women. All adults with Turner's syndrome should therefore be followed up by a multidisciplinary team to improve life expectancy and reduce morbidity.